Pengaruh Harga, Customer Review Dan Customer Rating Terhadap Minat Beli Pada Marketplace Shopee (Studi Kasus Pada Mahasiswa/I Universitas Nuku) - Rajak, Sahrila Abdul; Dahlan, Fadli; Majojo, Muhammad Yasin (Peneliti.net, 2025)
This research aims to determine the influence of price, customer reviews, and customer ratings on the purchasing interest of Nuku University students. This study uses a quantitative method. The population in this study is Nuku University students, totaling 515 people. The data analysis techniques used are validity and reliability tests, classical assumption tests (including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests), multiple linear regression, t-tests (partial tests), F-tests (simultaneous tests), and determination coefficient tests. The research results show that (1) price has a significant impact on purchase interest, (2) customer reviews do not have a significant impact on purchase interest, (3) customer ratings have a significant impact on purchase interest, and (4) price, customer reviews, and customer ratings have a simultaneous impact on purchase interest.